The effect of perception of value co-creation on customer satisfaction through perceived value and brand equity as moderating factors - Abror; Ilham (Marketing Management Studies, 2021)
This study aims to determine the effect of perception of value co-creation on customer satisfaction through perceived value and brand equity as a moderating effect on the promise of coffee consumers. This research was conducted on several customers who have visited and consumed the soul promise coffee. The analytical method used is a structural equation model (SEM). Based on the results of data processing that has been found, the results of hypothesis testing found that perception value co creation has a positive effect Perception value of co creation has a positive effect on customer satisfaction with perceived value as a moderating factor in consuming Kopi Janji Jiwa Padang. In the second hypothesis testing stage it was found that Perception of value co creation had a positive effect on customer satisfaction moderated by brand equity in consuming Kopi Janji Jiwa Padang.